La tradizione manoscritta dei Dialogi di Gregorio Magno. Nota su una recente ricognizione - Ronzani, Rocco (Augustinianum, 2013)
This contribution presents some results of recent research carried out on the Spanish manuscript tradition of the Dialogues of Gregory the Great (590-604). After a panoramic review of the present state of philological research and the expectations that such investigations have raised in the last three decades, this article analyses the situation of the Iberian manuscript tradition in general terms and afterwards illustrates the results of the research carried out on the so-called fragment of the Barcelona Dialogues (CLA 1626), a folio in uncial characters that transmits a passage of the Homilies on the Gospels of Gregory but which, nevertheless, offers the opportunity for some reflections on the lexis gregoriana. This article also offers some details concerning three codices in Visigothic characters from the libraries of La Seu d’Urgell, Santo Domingo de Silos and the British Library of London, which are either complete or which conserve large parts of the text. Finally, this investigation provides some hints concerning Spanish manuscripts in Carolingian characters which, as exemplars of the Vulgate text from the Frankish area, were completely unhelpful for the purpose of preparing a critical edition of the text.